IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH MAKE A MATCH TECHNIQUE TO THE SEVENTH GRADERS OF SMP NEGERI 40 PALEMBANG - Yuyun Hendrety; Heru Setiawan; Shelvi Carmelya (Didascein : Journal of English Education, 2021)
Vocabulary is learned through focused, conscious study, but even more commonly in an indirect manner through listening, reading and using context clues to figure out the meaning. However, this kind of incidental learning is only possible if the amount of unknown words remains low. The purpose of this study was to find out whether or not Make a Match technique was effective to improve students’ vocabulary mastery. In conducting this study, the researchers used quasi experimental research design. Test was used as the technique for collecting data. The data were analyzed by using paired and independent sample t-test. The population was all the seventh graders of SMP Negeri 40 Palembang in the academic 2019/2020. The researchers used purposive sampling technique and took the classes of VII.9 and VII.10 as the sample of the study. The result showed that make a match was effective to improve students’ vocabulary mastery. It was found that the value of t-obtained was higher than the critical value of r-table or the t-obtained was 6.998 then t-table was 1.999. Based on the result of the analysis, it is claimed that make a match technique was effective to improve students’ vocabulary mastery to the seventh graders of SMP Negeri 40 Palembang. Keywords: Make a match technique, vocabulary mastery